Analysis of the Flexing Phenomenon on Social Media from an Islamic Perspective - Rafli Maulana Lubis; Hasan Sazali (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
Flexing is a new phenomenon or culture in the current digital era to show off wealth on social media to increase social status and self-existence. This study aims to analyze the impact of the flexing phenomenon from the Islamic perspective, specifically for Muslims on social media. The method uses descriptive qualitative research with a phenomenological approach instrument that discusses a description of a phenomenon that appears in the social environment. The analysis uses Social Learning Theory and data collection methods with observation and literature study. The research's results with Islamic thought from the perspective of Social Learning Theory found several impacts that complete previous studies, specifically, 1). The formation of an attitude of flexing and arrogance, 2). The new paradigm of an understanding of materialism, and 3). Changing the orientation of the afterlife to the temporal. 4). Creating innovative criminality.